The Kina Model. A tool for exploring the spatial population development in China by large scale micro simulation - Peder Axensten; Zhongxin Chen; Shenghe Liu (European Regional Science Association (ERSA), 2004)
This paper is on work in progress. The China Model exists and runs fast and usually reliably although it still has very simple behavioural modules that do not produce very reliable results. The purpose of the paper is to present the structure, content, and current state of validity of the model.
Keywords: 330